Iatrogenicity : Causes and Consequences of Iatrogenesis in Cardiovascular Medicine - Akin, Ibrahim; Kostis, John B.; Gussak, Ihor (Book collections on Project MUSE., 2018)
Iatrogenesis is the occurrence of untoward effects resulting from actions of health care providers, including medical errors, medical malpractice, practicing beyond one's expertise, adverse effects of medication, unnecessary treatment, inappropriate screenings, and surgical errors. This is a huge public health issue: tens to hundreds of thousands of deaths are attributed to iatrogenic causes each year in the U.S., and vulnerable populations such as the elderly and minorities are particularly susceptible. Edited by two renowned cardiology experts, Iatrogenicity: Causes and Consequences of Iatrogenesis in Cardiovascular Medicine addresses both the iatrogenicity that arises with cardiovascular interventions, as well as non-cardiovascular interventions that result in adverse consequences on the cardiovascular system. The book aims to achieve three things: to summarize the available information on this topic in a single high-yield volume; to highlight the human and financial cost of iatrogenesis; and to describe and propose potential interventions to ameliorate the effects of iatrogenesis. This accessible book is a practical reference for any practicing physician who sees patients with cardiovascular issues. .